Correction: Efficacy, safety, and patient-reported outcome of immune checkpoint inhibitor in gynecologic cancers: A systematic review and meta-analysis of randomized controlled trials. - Fitriyadi Kusuma; Glenardi Glenardi; Ghea Mangkuliguna; Hariyono Winarto; Gatot Purwoto; Tofan Widya Utami; Tricia Dewi Anggraeni (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0307800.].